(untitled) (Faculty of Education Scientific Journal, 2024)
The current research aimed to review some of the deep roots of the crisis and alienation of sociology in the Arab world. Some have identified the roots of this crisis in that we apply the statements of Western social theories that arose in historical, geographical and cultural circumstances different from ours to solve our problems and social issues, which means the necessity of employing these theories in solving the problems of the Arab person in a way that suits his cultural specificity and his religious, heritage and historical reference. Indeed, there is no harm in establishing social theories that emerge from our heritage, history, and civilization, and here lies the essence of creativity that must be delved into. We have an undeniable advantage in that. The scholar Ibn Khaldun was a distinguished example in social theorizing and experimentation. Returning to the Arab and Muslim pioneers, we will notice that it is possible to lay the foundations for an Arab-Islamic science, especially since we were among the foundations of the Abbasid, Umayyad, and Andalusian civilizations, and we enlightened the